UN CASO DE SOCIABILIDAD EN ARAÑAS (ARANEAE: NESTICIDAE) OseAR GILEDE DEL PARQUE AMACAYACU, AMAZONAS (2013)
A case of sociability of spiders with observation of prey attack is recorded, in rain forest frorn colornbian Arnazony (Parque Nacional Natural Arnacayacu). There is a cooperative predatory behaviour and there is nota relationship between prey and spiders sizes. Behavioural sequences are described in wich work distribution in absence of hierarchy is identified, no intervention of males in capture processes is verified and inactivity periods in the colonies are analized, as well as spider web location. Further research will deep dernographic and behavioural aspects.